Dicey, Lubman, and Bagehot: Chinese Law in the Common Law Mind - Dowdle, Michael W. (Columbia Journal of Asian Law, 2005)
Surprising comparisons can yield surprising insights. One such comparison is the study of Chinese law with that of English constitutional history. It turns out that such a comparison can help explain one of the more curious aspects of Chinese legal studies in the United States: the relatively unique success of Chinese legal studies in embedding itself into present-day American legal academe.’ It can also help us better appreciate the germinal contributions of one of the foremost scholars of Chinese law, Stanley Lubman, both to our understanding of Chinese law, and to comparative legal studies more generally. One of the distinctive features of Lubman’s scholarship is his ability to reference Anglo-American legal history. As suggested by the title of this essay, I seek to show that a comparison of the evolution of English constitutionalism with the more recent evolution of Chinese legal studies in the United States reveals that Lubman is not only an accomplished student of this history, but is also in his own way an important part of this history.